A benefit to providing information? Flower size cues, plant attractiveness, and plant visit length. (3rd May 2019) - Essenberg, Carla J; Guevarra, Paige E; Moreau, Hadley M; Jordan, Cody J; Zisman, Talia
Abstract: In many plant species, flower size is correlated with the production of floral rewards such as nectar and pollen and, therefore, provides information to pollinators about flower quality. However, how relationships between flower size and rewards influence plant fitness is not well understood. In particular, it is unclear whether indicating to pollinators which flowers are unrewarding harms or benefits plants. We used a laboratory system with artificial flowers to examine bumblebees' ( Bombus impatiens ) responses to plants that had flower size as an informative cue (with large flowers rewarding and small flowers unrewarding) as compared with "deceptive" plants that had a mixture of rewarding and unrewarding large flowers and plants with only large, rewarding flowers. Bees had previously foraged in a context in which only large flowers provided rewards. Small flowers were visited less often than large flowers. In comparing plants with different numbers of flowers, we found that small flowers, although they added less to a plant's attractiveness than large flowers, did increase a plant's attractiveness if present in sufficient number. Furthermore, plants with informative cues received substantially fewer flower visits per plant visit in comparison with deceptive plants, even when the plants with informative cues had a larger number of flowers. Cues identifying unrewarding flowers could, therefore, reduce rates of within-plant pollen movement, increasing the plant's fitness gains per flower visit. Their contribution to whole-plant attractiveness and avoidance of inbreeding could help explain why many plants produce small, relatively unrewarding flowers even though pollinators avoid visiting them. Abstract : Small, unrewarding flowers contribute to a plant's attractiveness even though bees avoid visiting them. At the same time, having small flowers can cause bees to leave a plant earlier, reducing pollen movement within the plant. These findings, based on observations of foraging bumblebees, may help explain why many plants produce a mixture of larger, more rewarding flowers and smaller, less rewarding flowers, in spite of pollinators' avoidance of the smaller flowers.